1997
DOI: 10.1086/118271
|View full text |Cite
|
Sign up to set email alerts
|

The Butcher-Oemler Effect at Low Redshift: Spectroscopy of Five Nearby Clusters of Galaxies

Abstract: We present multi-fiber spectroscopy and broadband imaging of early-type galaxies in five nearby rich clusters of galaxies. The main purpose was to look for "abnormal" spectrum galaxies (i.e., post-starburst galaxies which have strong Balmer absorption lines and emission line galaxies) in nearby clusters that are similar to those found by Caldwell et al. (1993) in the Coma cluster. Three of the clusters were purposefully selected to have pronounced double structure in their spatial distribution of the galaxies.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
163
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(175 citation statements)
references
References 53 publications
10
163
2
Order By: Relevance
“…This number is in strong contrast with the value found from the catalogue of local clusters of Dressler & Shectman (1988) but is broadly consistent with a fraction of ∼15% found among lower luminosity galaxies in 5 low-z cluster by Caldwell & Rose (1997). The reason for the striking difference with the sample of Dressler & Shectman (1988) is probably due to the difference in the magnitude limit of the two surveys.…”
Section: The Properties Of the Post-starburst Populationsupporting
confidence: 48%
“…This number is in strong contrast with the value found from the catalogue of local clusters of Dressler & Shectman (1988) but is broadly consistent with a fraction of ∼15% found among lower luminosity galaxies in 5 low-z cluster by Caldwell & Rose (1997). The reason for the striking difference with the sample of Dressler & Shectman (1988) is probably due to the difference in the magnitude limit of the two surveys.…”
Section: The Properties Of the Post-starburst Populationsupporting
confidence: 48%
“…In some studies, post-starburst galaxies are found to be mostly bulge-dominated and/or have a morphology that is consistent with being early-type (Goto & SDSS collaboration 2003;Quintero et al 2004;Tran et al 2004;Blake et al 2004;Goto 2005;Balogh et al 2005;Poggianti et al 2009), and in some others have a high incidence of disks and spiral arms (e.g., Franx 1993;Couch et al 1994;Dressler et al 1994;Caldwell & Rose 1997;Dressler et al 1999). For example, Quintero et al (2004) visually inspected a sample of 160 galaxies from the SDSS at 0.05 < z < 0.20, and classified 90% of them as bulge-dominated systems.…”
Section: Morphologies and Structural Parametersmentioning
confidence: 99%
“…For instance, the relation between the VCS and cluster dynamical status has been explored in very few studies (Ribeiro et al 2010(Ribeiro et al , 2013. The member selection might be particularly critical in very active clusters, and the scenario is made more complex by the fact that cluster mergers might also enhance star formation in galaxies (e.g., Caldwell & Rose 1997;Ferrari et al 2005;Owen et al 2005). The dependence of VCS on redshift is also only rarely investigated.…”
Section: Introductionmentioning
confidence: 99%